Investigation of heat transfer and exergy loss in a concentric double pipe exchanger equipped with swirl generators - Akpinar, EK; Bicer, Y (Elsevier France-Editions Scientifiques Medicales Elsevier, 2005)
In this study, the effect on heat transfer rates, friction factor and exergy loss of swirl generators with holes for the entrance of fluid were investigated by placing them at the entrance section of inner pipe of heat exchanger. Various swirl generators having circular holes at different number and diameter were used. Hot air and cold water were passed through the inner pipe and annulus, respectively. Experiments were carried out for both parallel and counter flow models of the fluids at Reynolds numbers between 8500-17500. Heat transfer, friction factor and exergy analyses were made for the conditions with and without swirl generators and compared to each other. Some empirical correlations expressing the results were also derived and discussed. It was observed that the Nusselt number could increase up to 130% at a value of about 2.9 times increase in the friction factor by giving rotation to the air with the help of the swirl elements. The increase the dimensionless exergy loss was about 1.25 times in comparison with that for the inner pipe without swirl generators. (c) 2005 Elsevier SAS. All rights reserved.
Keywords: concentric heat exchanger; exergy loss; friction factor; NTU; swirl generator